Study the relationship between nasal polyps, platelet count, mean platelet volume, neutrophil/lymphocyte ratio in patients attending otolaryngology OPD in a tertiary care teaching hospital, West Bengal - Sharma, Manuprita; Raman, Santosh; Ray, Bidhan; Bagga, Rupali Verma; Sahu, Ramesh Kumar; De, Suajoy Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Nasal obstruction is a common cause of marked nasal septal deviation. It is related strongly with hypoxia. Hypoxic conditions increase mean platelet volume levels. Many studies in literature point out that inflammation related to nasal polyp is mostly dependent on eosinophils and their inflammatory products. Beside eosinophils, platelets may have a role in nasal polyp development. Platelets are involved in hemostasis, tissue repairing and inflammation. Recently, mean platelet volume (MPV) was recognized as a simple inflammatory marker in the inflammatory disease. This study investigated the relationship of nasal polyps with MPV (mean platelet volume), platelet count and NLR (neutrophil to lymphocyte ratio). Methods: The cross-sectional observational study we investigated CBC (complete blood count) parameters of the patients that consulted ENT clinic in a tertiary care teaching hospital, Haldia because of nasal polyp. About 76 patients and 42 controls were included in this study. In all groups, WBC (white blood cell count), RBC (red blood cell count), RDW (red cell distribution width), platelet count, MPV, PDW (platelet distribution width) and NLR parameters from CBC (complete blood count) were compared between patients and controls. Results: Mean WBC values were 6.89±1.33×103/μL in patients with NPs, vs. 7.11±2.32×103/μL in the control group. Mean haemoglobin (Hb) values were 13.19±1.34 g/dL in patients with NPs, vs. 14.1±1.67 g/dl in the control group. Mean MPV values were 9.11 ± 1.08 fL in patients with NPs, vs. 8.32±0.53 fL in the control group. Mean PLT values were 232.38 ± 39.97×103/μL in patients with NPs, vs. 271.44±45.14×103 in the control group. MPV was higher in nasal polyp patients, whereas platelet count was higher in controls. The difference was significant for the mean absolute neutrophil, platelet count, and lymphocyte counts, NLR, PDW and MPV values between the study group and the control group. Conclusions: Platelet count and NLR were significantly lower in patients than the controls, whereas MPV was significantly higher in nasal polyp patients.